2017
DOI: 10.1515/snde-2016-0117
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate misalignment and economic growth: evidence from nonlinear panel cointegration and granger causality tests

Abstract: We analyse the impact of exchange rate misalignment on economic growth for a sample of emerging economies from 1970 to 2014 using a panel smooth transition regression vector error correction model. Besides, we provide a granger causality test conducted in a non-linear framework. We find that a rise in misalignment increases significantly the output in the short-run when currencies are close to equilibrium. When they are highly misaligned, the impact on growth is reduced. However, no significant impact of outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Additional covariates are used. From Table 10, we can note that our variable of interest is positive and significant in all three Tipoy et al (2017b). 2.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Additional covariates are used. From Table 10, we can note that our variable of interest is positive and significant in all three Tipoy et al (2017b). 2.…”
mentioning
confidence: 88%
“…We use various estimators besides the usual panel data fixed effects (FE). The index of exchange rate undervaluation, which comes from the work of Tipoy, Breitenbach, and Zerihun (2017b), is computed using the cross-section autoregressive distributed lag (CS-ARDL) of Chudik, Mohaddes, Pesaran, and Raissi (2016). This estimator is robust to crosssectional dependence.…”
Section: Econometric Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of misalignments on economic activity seems to be nonlinear extending to other variables, including institutions. Similarly, Tipoy, Breitenbach and Zerihun (2018), sought to find the impact of misaligned exchange rates on economic growth for a sample of emerging economies using data from 1970 to 2014 and a panel smooth transition regression vector error correction model in addition to a Granger causality test within a nonlinear framework. They found that exchange rate misalignment affects output in both short and long run particularly when the currency is overvalued.…”
Section: Empirical Literaturementioning
confidence: 99%
“…A review of the literature 5 reveals that most studies dealing with the impacts of real exchange rate (RE) misalignment on trade flows of the United States with China (or other country studies) 6 have implicitly supposed that the impacts of RE misalignment on imports and exports are symmetric. A great number of recent empirical studies, however, suggests that the effects of RE misalignment on economic activity in general, and on trade flows in particular, are likely to be asymmetric (Béreauet al, 2012;Couharde, and Sallenave, 2013;Allegret and Sallenave, 2014;Tipoy and Zerihun, 2017;Wong, 2019;Cuestas et al, 2020). For example, Allegret and Sallenave (2014) estimated a GVAR model to assess the impacts of exchange rate misalignment on global imbalances for 15 developed and emerging economies using data for the 1980-2010 period.…”
Section: I-introductionmentioning
confidence: 99%